Prevalence of microalbuminuria with associated risk factors among diabetics in the urban field practice area of a medical college in Muzaffarnagar, Uttar Pradesh - Pandey, Prakhar; Singh, Nirankar; Farooq, Umer (International Journal Of Community Medicine And Public Health, 2020)
Background: Diabetes is a major threat to global public health that is rapidly getting worse and its biggest impact is on adults of working age 45-55 in developing countries. Diabetes mellitus causes progressive changes to the kidneys and ultimately results in diabetic nephropathy. Microalbumin measurement is useful in diagnosis at an early stage, before the development of proteinuria. Methods: This is a community based cross sectional study. The study period of 2 months, from September 2019 to October 2019. Adult between 20 to 59 years of age at the time of data collection from house to house visit were included in the study. A total of 138 diabetics were found in the community and accessed for microalbuminuria and other risk factors. Results: Prevalence of microalbuminuria among was 15.1%. Logistic regression model analysis revealed that micro albuminuria was significantly correlated with the diastolic blood pressure (p=0.003) and the duration of diabetes (p=0.001). Conclusions: Due to the high prevalence of diabetes in India we need to screen all diabetics for microalbuminuria. Control of blood pressure should also be done more vigorously in diabetic patients.